The repercussions of cyberbullying on students on educational platforms - Alturif, Ghada; Alsand, Hessa (Frontiers in Psychology, 2024)
The study aimed to explore the repercussions of cyberbullying on students on educational platforms. This descriptive study depends on a social survey for a sample of male and female students in their high school. The sample is 824 people, and data was collected through a questionnaire. The paper studies the repercussions of cyberbullying on students and the educational atmosphere. The study's outcome is that most of the sample's participants agree on these repercussions on both, students and the educational atmosphere. The study recommended holding conferences, webinars, and workshops, handling the repercussions of cyberbullying and regulations for bullies on educational platforms to deter this cyberbullying, to raise awareness among students.